Analisis strategi pengembangan Usaha Mikro Kecil dan Menengah di era teknologi pada Industri Keripik Tempe Sanan Malang - Bimo, Farel Aryo (Maliki Interdisciplinary Journal, 2024)
This research aims to examine the factors that are the main attraction of marketing programs and measure the extent to which a marketing element is implemented in the marketing strategy of Micro, Small, and Medium Enterprises. Information about marketing elements was obtained from the results of in-depth interviews and field observations where the source of the information is the informant. The research results show that the marketing strategy for Malang UMKM Sanan tempe chips is to diversify products by producing various types of chips, introducing branded varieties so that consumers have many choices, and producing chips in different weight compositions and packaging, building a network. Resellers to expand sales areas, introduce products at various bazaars and important events in East Java Province, as well as promote products via social media.